Effects of stacking sequence of the layers on deformation behavior and microstructure evolution of Ti/Ni laminated metal composites - Jie Zhao; Bing Zhang; Tianli Zhao; Zhijuan Zhang; Zhiqiang Lei; Zhaolin Wang; Zengwen Zhang; Shancheng Zhan; Longjie Dang; Kuaishe Wang (Journal of Materials Research and Technology)
The effect of stacking sequence of the layers on the deformation behavior, microstructure evolution, and mechanical properties of Ti/Ni laminated metal composites (LMCs) fabricated by roll-bonding was studied. The results indicated that Ti/Ni/Ti exhibited the characteristics similar to that of work hardening, while Ni/Ti/Ni predominantly demonstrated the traits akin to that of dynamic recovery. The deformation compatibility of Ti/Ni/Ti is better, exhibiting smaller interfacial additional shear stress and a more even strain distribution among the component layers. By the analysis of strain field, the friction force between the rollers and the plates causes the intensive shear deformation in the outer layer, leading to microstructure characterized by more elongated grains and higher dislocation densities. The velocity field shows that the rheological difference between the component layers of Ni/Ti/Ni is more significant, especially at the exit, which can disrupt the bonded interface and diminish bonding quality. The interfacial shear strength, elongation (EL), and ultimate tensile strength (UTS) of Ti/Ni/Ti are found to be higher. These findings can provide novel insights and theoretical guidance for the fabrication of LMCs.